THE INFLUENCE OF RECRUITMENT, WORK ABILITIES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN REGIONAL VI STATE PERSONNEL AGENCY (BKN) MEDAN CITY - Desi Andriyanti Br. Simamora; Juliana Elisabeth Br. Sinurat; Enita Dearni Purba; Syakina Falshabilla Adisty Lubis; Cut Fitri Rostina; Fauzi (Mount Hope Economic Global Journal, 2024)
This research was conducted at the State Civil Service Agency (BKN) Regional VI Jl. TB. Simatupang No. 124, Sunggal, 20127, District. Medan Sunggal, Medan, North Sumatra. Sampling in this research used a saturated sampling method or often also called a census. The population in this study was 96 Civil Servants. The research results show that: (1) partially the recruitment variable has a positive and significant effect on employee performance (2) partially the work ability variable has a positive and significant effect on employee performance (3) partially the work discipline variable has a positive and significant effect on employee performance ( 4) simultaneously there is a positive and significant influence between the variables of recruitment, work ability and work discipline on employee performance. The result of the R-Square Determination Coefficient is 0.528. This means that the influence of the independent variables recruitment, work ability, work discipline on the dependent variable employee performance is 52.8%. Meanwhile, the remaining 47.2% was influenced by other variables not examined in this research. For example, work morale, work environment and leadership